2016
DOI: 10.1186/s13000-016-0475-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular adenoma classification: a comparative evaluation of immunohistochemistry and targeted mutational analysis

Abstract: BackgroundFour subtypes of hepatocellular adenomas (HCA) are recognized: hepatocyte-nuclear-factor-1α mutated (H-HCA), β-catenin-mutated type with upregulation of glutamine synthetase (b-HCA), inflammatory type (IHCA) with serum-amyloid-A overexpression, and unclassified type. Subtyping may be useful since b-HCA appear to have higher risk of malignant transformation. We sought to apply subtype analysis and assess histological atypia, correlating these with next-generation sequencing analysis.MethodsTwenty-six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
3
24
1
Order By: Relevance
“…We presented the case of a young woman with a history of oral contraceptive use who initially presented with discrete symptoms and an ultrasonography result suggestive of a liver lesion. It is known that HCA affects mainly women using oral contraceptives [ 3 ], in keeping with our patient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We presented the case of a young woman with a history of oral contraceptive use who initially presented with discrete symptoms and an ultrasonography result suggestive of a liver lesion. It is known that HCA affects mainly women using oral contraceptives [ 3 ], in keeping with our patient.…”
Section: Discussionsupporting
confidence: 84%
“…Hepatocellular adenomas (HCAs) are rare monoclonal benign liver tumors that most commonly occur in women (3–4 per 100,000 women) [ 1 , 2 ]. HCAs are the third most prevalent benign tumors of the liver and have the capacity to undergo malignant transformation [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as Table 4 shows there have been many controversial reports about the percentage of β-catenin mutated HCAs. Studies from the USA report the results of b-HCA from zero (2) to 15.4% (14) which can be secondary to variable ethnicity in this country. Studies from Japan are more consistent and two reported studies have had similar results around 15% (12, 13).…”
Section: Discussionmentioning
confidence: 91%
“…2019; 19(6):e91641. means that the issue is evolving and the difference in the frequencies is multifactorial, which emphasizes the importance of routine classification of the cases with the diagnosis of HCA (4,(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological and immunohistochemical analysis was done first, we attempted to classify each adenoma based on IHC pattern, as previously described (10 ). HA with strong and diffuse GS staining (score 2+) and/or β-catenin nuclear staining, regardless of the SAA staining status, were categorized as HA-B.…”
Section: Resultsmentioning
confidence: 99%